ANALISIS PENGARUH PERIKLANAN DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA ROKOK MARLBORO PT. HM SAMPOERNA TBK. (Studi pada Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro Semarang) - Iqbal Agil Prasidda; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2017)
The sales volume of cigarettes in Indonesia continues growing, as the average daily cigarette consumption per person continues to increase. Marlboro Cigarettes leads the market in the SPM segment (Sigaret Putih Mesin) in Indonesia, but the SPM Share of market has decreased and market share based on Marlboro cigarette sales volume decreased in 2014. This is due to the market trend that still enjoys kretek cigarettes SKM (Sigaret Kretek Mesin) rather than foreign cigarettes such as Marlboro, as well as competitive advertisement competition by competitors and the goverments restriction rule on advertising on cigarettes. The type of research is explanatory research, with a population of 100 respondents who buy and consume brand cigarettes Marlboro. Sampling in this study using non-probability sampling. The sampling technique uses Incidental sampling. Data were collected through questionnaires. Data analysis techniques used are cross tabulation, correlation, simple regression, and multiple regression using SPSS 24.0 application. This study concludes that advertising and lifestyle influence purchasing decisions, either partially or simultaneously. Lifestyle variables have greater influence than advertising variables. Based on this, researchers suggest that additonal and maximizing the Marlboro cigarette advertising medium by increasing the frequency of ads, serving ads, and strategically placing ads. In addition, held a promotional event Marlboro cigarettes in place of youth crowd.